Investigation of the effect of 131I on blood parameters for thyroid cancer treatment - Khandaker, Mayeen Uddin *; Hassanpour, Mehdi; Khezripour, Saeedeh; Rezaei, Mohammad Reza; Bazghandi, Atefeh; Hassanpour, Marzieh; Faruque, Mohammad Rashed Iqbal; Bradley, D.A. * (Elsevier, 2023)
Hematopoiesis plays a significant role in mammals’ life. Hematopoietic damage due to radiations of different arrays, such as ionizing and non-ionizing radiations, could lead to external infections, internal infections, and anemia. Different cancers’ treatment using radioactive sources affects the blood parameters (i.e., mature cells, immature cells, and stem cells). In the present paper, the effect of intravascular injection of Iodine-131 (131I) on the blood parameters for thyroid cancer treatment has been investigated utilizing the MCNPX code and Runge-Kutta fourth-order method. The simulation results showed that the accumulated absorbed dose in adult phantom (ORNL whole body phantom) due to normalized intravascular injection of 1 mCi (mCi) of 131I was 1.97 × 10